Current State of Watersheds Planning in the Department of Sucre (Colombia) - Hernández Arrázola, Angelina María (Corporación Universitaria del Caribe, CECAR., 2018)
ABSTRACT The state of the main water sources of the Department of Sucre; the deterioration that is evident in the fauna, flora and populations surrounding them; and the lack of information on the management of territories considered as special ecosystems, in this case in particular, the areas belonging to watersheds, shows the state of the planning of these in the Department. This situation warns of the need for a quick order, which allows maintaining or restoring the balance between the use of the ecological services of the water basins and the natural state of the same.